PENERAPAN MEDIA PEMBELAJARAN WORDWALL PADA MATA PELAJARAN IPAS TERHADAP HASIL BELAJAR SISWA KELAS V DI UPT SD NEGERI 11 TURATEA KABUPATEN JENEPONTO - Sitti Ramadhani; Maruf; Nurfadilah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem in this study is how to apply wordwall learning media to see student learning outcomes. Problems were found in the form of a decrease in student learning interest at UPT SD Negeri 11 Turatea. This study aims to determine the application of wordwall learning media in science subjects on the learning outcomes of fifth grade students at UPT SD Negeri 11 Turatea, Jeneponto Regency. This type of research uses an experimental method with a quantitative approach. With the type of One-Group-Pretest-Posttest-Design research with the aim of knowing whether there is a significant increase in the learning outcomes of students in the UPT SD Negeri 11 Turatea. The sample in this study was fifth grade students of UPT SD Negeri 11 Turatea with a total of 18 students consisting of 10 girls and 8 boys. The data collection technique used was the initial test (pretest) and the final test (posttest) to determine the application of Wordwall Learning Media in the subject of Science on the learning outcomes of fifth grade students at UPT SD Negeri 11 Turatea, Jeneponto Regency. The results of this study indicate that the application of Wordwall Learning Media in the subject of Science on the learning outcomes of fifth grade students at UPT SD Negeri 11 Turatea, Jeneponto Regency. This situation can be seen from the test results which show that student learning outcomes before being given treatment are relatively low, namely the pretest result is 56% and after being given treatment the average posttest value is 84%. Based on the results of the study above, it can be concluded that the results of students' science learning at UPT SD Negeri 11 Turatea through the application of Wordwall Learning Media have increased.